Hypoxia: Role of SIRT1 and the protective effect of resveratrol in ovarian function. (2nd December 2021) - Nishigaki, Akemi; Tsubokura, Hiroaki; Tsuzuki‐Nakao, Tomoko; Okada, Hidetaka
Abstract: Background: Ovarian function is closely related to the degree of vascular network development surrounding the ovary. Maternal aging‐related construction defects in this vascular network can cause ovarian hypoxia, which impedes oocyte nutrient supply, leading to physiological changes in the ovaries and oocytes. The anti‐aging gene Sirtuin 1 (SIRT1) senses and adapts to ambient stress and is associated with hypoxic environments and mitochondrial biogenesis. Methods: The present study is a literature review focusing on investigations involving the changes in SIRT1 and mitochondrial expression during hypoxia and the cytoprotective effects of the SIRT1 activator, resveratrol. Main findings: Hypoxia suppresses SIRT1 and mitochondrial expression. Resveratrol can reverse the hypoxia‐induced decrease in mitochondrial and SIRT1 activity. Resveratrol suppresses the production of hypoxia‐inducible factor‐1α and vascular endothelial growth factor proteins. Conclusion: Resveratrol exhibits protective activity against hypoxic stress and may prevent hypoxia‐ or aging‐related mitochondrial dysfunction. Resveratrol treatment may be a potential option for infertility therapy. Abstract : Resveratrol may prevent mitochondrial dysfunction due to hypoxia or aging and that resveratrol treatment may be a potential therapy for treating infertility.